(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
This article is a personal homage to the life and work of Jean Genet - playwright, novelist, poet, essayist, and tangential existentialist. His work is as countercultural today as it was when it first appeared, for it presents profound and unsettling questions to contemporary culture; it challenges its cherished values – identity, nationality, property, gender, fidelity. For these reasons it also presents a formidable if indirect challenge to psychotherapy, a profession presently undecided as to what its function might be, whether providing a sedative which will make people more docile or instead helping human beings to become freer, find meaning in their lives and negotiate their relationship with what Rollo May called "the daimonic". As charted by Sartre in his Saint Genet, the life of Jean Genet provides not so much a role-model but a heart-rending, contradictory, flawed and deeply human example of realizing one’s creative potential against all odds.